Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Effect of mesoscopic pore structure on the leaching behavior of ion-adsorption rare earth ores - Yujun Luo; Guanshi Wang; Fuming Lin; Shili Hu; Jun Zhang; Wenjun Du (Hydrometallurgy, 2026)

Photothermal antibacterial bilayer films from konjac glucomannan/shellac: A Prussian blue-engineered strategy for preservation of fresh-cut Benincasa hispida - Xin Lei; Yueguang Wang; Xianrui Chen; Jing Zhang; Xuan Lin; Wenjun Guo; Xiuqing Guan; Chengrong Wen; Di Zhang; Lin Wang; Jie Pang (Food Research International, 2026)

Broad-spectrum defluorination via electronic strain of carbon–fluorine bonds: a ‘fluorophilic’ zero-valent metal system - Lisha Yang; Tong Hu; Dong Zhang; Wenjun Zhou; Daohui Lin (Water Research, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Co-degradation detoxification of dichloromethane and n-hexane in a microbial electrolytic cell: metagenomic insights into degradation pathways and functional genes - Meng Wu; Hongfeng Lu; Wenjun Lin; Jun Hu; Zhiliang Yu; Jianming Yu (Journal of Environmental Chemical Engineering, 2026)

A hybrid soft sensing framework for cost-effective monitoring of nitrogen in wastewater treatment under data scarcity - Yaorong Shu; Zhilin Li; Jinpeng Chen; Xiaoyu Lin; Wenjun Liu; Juan Mao; Hui Liu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu (Journal of Environmental Chemical Engineering, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Acquirement of white Chlorella vulgaris mutant through zeocin mutagenesis and estimation of its high-density fermentation - Chunlei Tang; Lu Li; Wenjun Zhou; Lin Chen; Tianzhong Liu; Xuefeng Lu (Algal Research, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Assessing the impact of rotifers on biomass production of microalgae and cyanobacteria - Lin Chen; Maruthanayagam Veerabadhran; Yanfei Pan; Xiang Liu; Wenjun Zhou; Guodong Luan; Tianzhong Liu; Xuefeng Lu (Journal of Applied Phycology, 2026)

A difference-characteristics-based de-spiking approach for ADV velocity data under unsteady flow conditions - Yue Chen; Ping Gong; Wenjun Yang; Haili Lin (Ocean Engineering, 2026)

Interatomic push-pull engineering in heterocyclic covalent organic frameworks for boosting photocatalytic hydrogen peroxide production - Wenjun Yang; Jialong Lv; Yuelin Chen; Weikang Peng; Shibin Zheng; Wei Lin; Jinhong Bi; Guocheng Huang (Chemical Engineering Journal, 2026)

Optimizing solvation structure of electrolyte to improve ion transport and reduce interphase resistance for fast-charging Li-ion batteries - Yiyi Zheng; Jiapei Li; Tian Zhang; Shuyu Dong; Qiaohui Duan; Zhiqiang Guan; Dewu Lin; Wenjun Zhang; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Breaking the lifespan bottleneck: How do microbes enable the long-term removal of per- and polyfluoroalkyl substances in biological activated carbon filters? - Huijuan Li; Jie Yuan; Nile Wu; Wenjun Sun; Zedong Lu; Jiajia Wang; Lin Tang (Chemical Engineering Journal, 2026)

Spatially explicit nutritional landscapes couple with environmental variables to shape nekton distribution patterns - Na Zang; Wenjun Zheng; Bilin Liu; Shaoqin Wang; Xinjun Chen; Dongming Lin (Limnology and Oceanography, 2026)
Species distributions are traditionally explained by environmental gradients, yet the role of nutritional factors, particularly essential fatty acids (EFA), remains poorly understood. We test the hypothesis that zooplankton EFA form a nutritional landscape that couples with environmental variables to shape the biogeography of nekton. We integrated spatial data of zooplankton EFA (arachidonic acid (ARA, 20:4n‐6), eicosapentaenoic acid (EPA, 20:5n‐3), and docosahexaenoic acid (DHA, 22:6n‐3)) with environmental variables into joint species distribution models (JSDMs). We compared explanatory power across three model types: JSDM_Env (environmental variables only), JSDM_EFA (EFA variables only), and JSDM_EnvEFA (combined environmental and EFA variables). Spatial analysis revealed significant heterogeneity in EFA concentrations, with elevated levels of EPA and DHA concentrated in the northeastern region. Model results showed that both EFA and environmental variables were effective predictors of species distributions. The JSDM_EnvEFA model exhibited the greatest explanatory power (mean AUC = 0.96, mean R 2 = 0.40), with variance decomposition revealing that EFA explained more variance than environmental variables (EFA: 54%, environment: 32%). Notably, EPA contributed up to 37% of the total explained variance, surpassing the influence of sea surface temperature (14%). Incorporating EFA also changed the estimated strength of species associations, suggesting that co‐occurrence patterns may be shaped by shared nutritional dependencies. Our results demonstrate that EFA availability is as critical as environmental variables in determining nekton species distributions, which support the spatial coupling hypothesis, demonstrating that EFA landscapes couple with environmental variables to structure pelagic communities. These findings establish nutritional landscape as a critical dimension of marine biogeography, providing a novel framework for predicting community responses to global change.

Contrasting Resource-Use Strategies Under Tropical Stress: Linking Leaf Functional Traits to Fruit Biomass and Oil Yield in Camellia Oleifera - Wenjun Hong; Jindian Yang; Shufen He; Jiaming Song; Weiyu Chen; Zhitong Mai; Feifei Chen; Ling Lin; Chuanteng Huang (Tropical Plant Biology, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

SIGMAR1 Drives the Development of Neuropathic Pain by Promoting AMPA Receptor Membrane Trafficking Through Interacting with NPTX1 in Male Mice - Jie Ren; Yasi Zheng; Wu Yang; Xueli Yin; Guanxi Liu; Ting Xu; Jianbo Zhang; Wenjun Xin; Xueqin Zhang; Suyan Lin (Neuroscience Bulletin, 2026)

Clustered ionic assignment enables simplified-robust monitoring of nitrate-based photoautotrophic microalgal growth - Yongqiang Wang; Lu Li; Qirui Huang; Wenjun Zhou; Lin Chen; Tianzhong Liu; Xuefeng Lu (Algal Research, 2026)

Sulfonate-mediated hydrogen-bond network modulation and proton enrichment at zerovalent iron-water interface for efficient hydrodechlorination reaction - Tong Hu; Zhendong Zhao; Lisha Yang; Huiwang Dai; Yuejin Zhang; Hao Li; Wenjun Zhou; Daohui Lin; Lizhong Zhu (Water Research, 2026)

Quantifying evapotranspiration and shading cooling of urban vegetation across climates under extreme heat using an integrated SCOPE-SEB model and surface temperature analysis - Zhaowu Yu; Mingchuan Shao; Wenjun Yang; Yujia Zhang; Yuxia Hu; Wenjuan Ma; Junhong Zhong; Yanghan Lin; Mincong Wang; Huiwen Zhang; Jiquan Chen; Chenghao Wang; et al. (Remote Sensing of Environment, 2026)

Non-radical PMS activation for simultaneous nitrite and sulfamethoxazole removal with inhibited nitrobyproduct formation - Jiawei Lin; Wenjun Zhou; Jiaqi Peng; Yongyou Hu; Hongfeng Zhang; Cheng Zhao; Qi Shan; Hao Zhou; Yi Yin (Journal of Water Process Engineering, 2026)

A systematic review and meta-analysis comparing the health burden of extreme heat and cold on mortality and urgent care utilization - Zhongguo Huang; Junrong Ma; Randy Tangang; Stephanie K. Zaloom; Wenjun Ma; Xiaobo Xue Romeiko; Shao Lin (International Journal of Hygiene and Environmental Health, 2026)

Turbulent flame structures of premixed prevaporized n-heptane/air in thin and broken reaction zone regimes - Wenjun Lin; Hongchao Dai; Xiao Cai; Limin Su; Jinhua Wang; Zuohua Huang (Fuel, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

An LLM-driven Agent framework for resilient modulus prediction: Integrating modified consistency index model and residual compensation - Xuanxuan Chu; Wenjun Zhang; Ling Zhao; Lin Tang; Hongjian Cai; Chengchao Guo (Transportation Geotechnics, 2026)

A data-driven comparative risk assessment of marine traffic accidents using an object-oriented Bayesian network - Xue Yang; Zhiying Lin; Wenjun Zhang; Sheng Xu; Shenping Hu (Ocean Engineering, 2026)

Aridity governs biogeographic patterns of soil fungal communities on the Qinghai-Tibet Plateau - Wenjun Xiong; Lin Xu; Chaonan Li; Changting Wang; Xiangzhen Li (Fungal Ecology, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Spatial-temporal patterns and multi-scale drivers of allergenic pollen Fraxinus, Platanus and Humulus in the urban and suburban area of Beijing, China - Xiaoxin Qin; Jianqin Xu; Yiyin Li; Xiao Yun; Hongxing Zhang; Wenjun Liu; Xinyi Zhao; Nan Lin (Urban Forestry & Urban Greening, 2026)

Intercropping reduces soil erosion, improves soil conditions, and increases productivity of a Camellia oleifera plantation - Zeyao Zhao; Lin Chen; Wanwan He; Wenjun Xie; Byron B. Lamont; Longsheng Chen; Li Mei; Zhaogui Yan (Plant and Soil, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Life-cycle assessment of ship electrification in the Yangtze River: Environmental and economic trade-offs - Chunhui Zhou; Wenjun Jia; Lin Jia; Yuanqiao Wen; Liang Huang; Wuao Tang; Hongxun Huang; Lichuan Wu (Ocean Engineering, 2025)

Impact of KCl and L-Arg substitution on low salt beef patties: oxidative, textural, flavor, and microbial insights - Chuanlong Yu; Lingli Chen; Hui Chen; Suyun Lin; Wenbing Hu; Kehui Ouyang; Wenjun Wang (Food Chemistry, 2025)

A multi-task deep attention network for simultaneous rapid quantification of sucrose, glucose, and fructose contents in pumpkin using FT-NIR spectroscopy - Yingchao Xu; Jiayu Luo; Shudan Xue; Huihui Han; Wenlong Luo; Wenjun Liu; Qingmin Jin; Huijing Lin; Baoling Chen; Yingyin Lin; Rong Zhang; Yujuan Zhong (Food Chemistry, 2025)

Ozone serve as mediator and effect modifier in the temperature-eGFR association: A longitudinal study on health examination cohort - Zhongguo Huang; Jinlu Lu; Guanhao He; Jianxiong Hu; Xuming Guo; Mingxuan Chen; Tao Liu; Shao Lin; Fanna Liu; Ying Xu; Yuan Song; Wenjun Ma (Environmental Research, 2025)

Bidirectional interphase modulation of ionic liquid-based additive for highly compatible thin-film lithium-metal batteries - Wenjun Lin; Haoyang Yuan; Tao Huang; Aishui Yu (Chemical Engineering Journal, 2025)

ML385 increases ferroptosis via inhibiting Nrf2/HO-1 pathway to enhances the sensitivity of MCF-7 TAMR to tamoxifen - Jie Yuan; Wenjun Huang; Minxia Lin; Shishen Sun; Fei Zhong; Lei Ye; Hao Yin; Xiaowei Ou; Zhiqiang Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

An Introduction to the Synthesis Community Integrated Model Version 2 (SYCIM2.0) and Its Simulation of the East Asian Summer Monsoon - Wenjun Liang; Wenjie Dong; Danya Xu; Bin Wang; Li Liu; Yanli Tang; Jie Yang; Song Wang; Fuhai Dao; Duofan Zheng; Chenhao Li; Fei Liu; et al. (Advances in Atmospheric Sciences, 2025)

Quaternary paleogeographic reconstruction of the Qaidam Basin, northern Tibetan Plateau - Xue Ke; Zongyan Zhang; Taizhong Song; Wenjun Yang; Jing Li; Feng Chen; Jinming Zhang; Xiaojin Zhang; Bowen Song; Qixiang Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Progress analysis of multi-dimensional perspective research on green ships: A knowledge graph-based approach - Chunhui Zhou; Lin Jia; Wenjun Jia; Wuao Tang; Hongxun Huang; Lichuan Wu (Marine Pollution Bulletin, 2025)

The current and future temperature-related mortality burden of cause-specific kidney diseases: A national case-crossover study in China - Mengen Guo; Jinlei Qi; Guanhao He; Jiangmei Liu; Jianxiong Hu; Peng Yin; Tao Liu; Ziqiang Lin; Fengrui Jing; Jinling You; Wenjun Ma; Fanna Liu; et al. (Environmental Research, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Influence of sidewall restriction on ceiling temperature distribution induced by double fires in a channel: Experimental and numerical investigations - Shengzhong Zhao; Kai Du; Yongzheng Yao; Tiantian Xu; Fei Wang; Lin Xu; Wenjun Lei (Tunnelling and Underground Space Technology, 2025)

Euglena gracilis fermentation and kinetic scaleup using ethanol as substrate for β-1,3-glucan paramylon production - Lu Li; Pengsen Zhao; Jiang Yu; Yongqiang Wang; Wenjun Zhou; Lin Chen; Zhaohui Zhang; Tianzhong Liu; Xuefeng Lu (Chemical Engineering Journal, 2025)

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Porous platinum nanozyme-amplified capacitance immunoassay for alpha-fetoprotein with hepatocellular carcinoma on an interdigitated gold micro-comb array - Huaxi Ma; Dongqing Zhang; Ting Lin; Shenglong Lin; Wenjun Wu; Ziyuan Liao; Xiangmei Wang; Haibing Gao (Analytica Chimica Acta, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Long-term characteristics of formaldehyde concentrations in four Chinese residences and estimation of annual average - Jin Ye; Zhiyuan Wang; Tao Yu; Wenbin Zhuang; Wenqing Lai; Lei Tian; Wenjun Leng; Ying Song; Shaodan Huang; Yinping Zhang; Cong Liu; Bencheng Lin (Building and Environment, 2025)

Quercetin rescues dihydrotestosterone-treated human dermal papilla cells via SHP2/AKT signaling to suppress autophagy and apoptosis - Ting Guo; Wenyu Li; Wenjun Zheng; Youkun Lin; Sijian Wen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Sedimentary geochemical records of the palaeovegetation and palaeoclimate evolution in the Pinghu Formation, Western Slope Belt, Xihu Sag, East China Sea Basin - Yanan Wang; Lin Wei; Xiong Cheng; Hui Diao; Wenjun Li; Dujie Hou; Jiansheng Li (Organic Geochemistry, 2025)

Leveraging ionic information for machine learning-enhanced source identification in integrated wastewater treatment plant - Yaorong Shu; Fanming Kong; Xiaoyu Lin; Jinpeng Chen; Wenjun Liu; Zhilin Li; Juan Mao; Xiaohui Wu (Journal of Water Process Engineering, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Regulating crystallization kinetics in high-performance perovskites solar modules via vapor seed layer engineering - Juan Zhang; Bingchen He; Jin Huang; Lin Yang; Yian Ding; Wenjun Zhang; Yukun Guo; Lei Shi; Abuliti Abudula; Weizhi Du; Xiaogang Hao; Xiaofei Ji; et al. (Chemical Engineering Journal, 2025)

WRKY transcription factor MdWRKY71 regulates flowering time in apple - Mengyu Su; Yi Yang; Caicai Lin; Wenjun Liu; Xuesen Chen (Plant Molecular Biology, 2025)

Synergistic effects of nutrient supplements and cell types on heterotrophic growth of Haematococcus pluvialis and enhanced photoinduction for astaxanthin accumulation - Danyue Zhao; Maruthanayagam Veerabadhran; Lin Chen; Wenjun Zhou; Tianzhong Liu (Journal of Applied Phycology, 2025)

Novel high-performance endothermic fuels from quasi-homogeneous nano-engineering - Ji Mi; Peilun Wang; Hongshang Wang; Chongkun Shao; Zhiyuan Yuan; Jingkai Ma; Yongsheng Guo; Xufeng Lin; Wenjun Fang (Fuel, 2025)

Unintentional emissions of polychlorinated naphthalenes in China: Sources, composition, and historical trends - Ye Huang; Lin Huang; Ying Li; Nazupar Sidikjan; Yunshan Zhang; Yan Chen; Yangmin Chen; Ye Li; Wei Du; Long Chen; Yan Wu; Shanshan Zhang; et al. (Journal of Environmental Sciences, 2025)

Effects of combustor wall temperature on the outer recirculation zone combustion modes transition in lean premixed DME/air swirling flames - Wenjun Lin; Weijie Zhang; Zhenhua An; Jinhua Wang; Zuohua Huang; Huangwei Zhang (Fuel, 2025)

Harnessing CuCoOX-Modified copper phenylacetylene for enhanced activation of peroxymonosulfate in non-radical sulfisoxazole degradation: Performance, pathways, and mechanisms - Wenjun Li; Daguang Li; Zili Lin; Yuchun Hong; Yishun Wang; Guangzhi Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Environmental Pollution, 2025)

BMSC Derived Exosomes Attenuate Apoptosis of Temporomandibular Joint Disc Chondrocytes in TMJOA via PI3K/AKT Pathway - Wenjun Chen; Futing Huang; Baoyi Chen; Huiyi Lin; Guan Luo; Weijun Zhang; Xiaoyu Zhang; Beining Zheng; Ziyi Wang; Shiting Wei; Jiaxin He; Chang Liu (Stem Cell Reviews and Reports, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Enhanced hydrodeoxygenation of lignin-derived phenolic compounds by regulating support composition of Ni/Al2O3-C catalyst - Shan Jiang; Qian Zhang; Xizi Lin; Wenjun Liu; Songbai Qiu; Riyang Shu (Fuel, 2025)

Microfluidic-engineered portable microsphere sensors for multi-mycotoxins detection - Xiaorui Wang; Gaowa Xing; Zengnan Wu; Haifeng Lin; Yongning Lin; Jiaxu Lin; Yaoshuang Xie; Wenjun Liao; Ling Lin (Chemical Engineering Journal, 2025)

A method for landslide identification and detection in high-precision aerial imagery: progressive CBAM-U-net model - Hanjie Lin; Li Li; Yue Qiang; Xinlong Xu; Siyu Liang; Tao Chen; Wenjun Yang; Yi Zhang (Earth Science Informatics, 2024)

Oerskovia flava sp. nov., a deoxynivalenol (DON)-degrading actinomycete isolated from the rhizosphere soil of long-term continuous cropping cucumber - Wei Wei; Wenjun Guo; Biyue Yang; Kaili Wang; Xinyu Hu; Guanya Ji; Xiangru Xu; Shenkui Liu; Lin Zhu (Antonie van Leeuwenhoek, 2024)

Nocardioides limicola sp. nov., an alkaliphilic alkane degrading bacterium isolated from oilfield alkali-saline soil - Lin Zhu; Biyue Yang; Wenjun Guo; Xinyu Hu; Shenkui Liu; Xiang Xiao; Wei Wei (Antonie van Leeuwenhoek, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Unraveling the tectonic and climatic influences on River Erosion: A late Quaternary case from the Dongda River, northeast tibet - Xiu Hu; Jinghao Lei; Weitao Wang; Yiran Wang; Youli Li; Peizhen Zhang; Kairong Lin; Wenjun Zheng; Qingri Liu; Fei Liu; Hao Liang; Yang Wang; et al. (Journal of Asian Earth Sciences, 2024)

Effect of partial substitution of NaCl by KCl on aggregation behavior and gel properties of beef myosin - Chuanlong Yu; Lingli Chen; Kehui Ouyang; Hui Chen; Mingsheng Xu; Suyun Lin; Wenjun Wang (Food Chemistry, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Light footprint of microalgae cultivation system addressed by modified Cornet model - Lu Li; Yongqiang Wang; Wenjun Zhou; Zhifei Yu; Guodong Luan; Lin Chen; Tianzhong Liu; Xuefeng Lu (Bioresource Technology, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Deep mineralization of bisphenol A via Cu–Mn spinel oxide nanospheres anchored N-doped carbon activated peroxymonosulfate - Xiaobo Wang; Lin He; Yu Zhou; Nan Wang; Lihua Zhu; JunTao Yan; Deng Ding; Wenjun Zhu; Xiaohua Zuo; Jinpeng Wang; Xiaoyong Wu (Chemical Engineering Journal, 2024)

Genetic engineering tools for the filamentous microalga Tribonema minus - Jianing Wang; Wenjun Zhou; Lin Chen; Tianzhong Liu; Xuefeng Lu (Algal Research, 2024)

Urban mangroves at risk: Understanding organophosphate flame retardant pollution at different urban function zones in shenzhen - Wenjun Zhao; Bing Li; Ruili Li; Xiaofeng Wu; Guanghui Lin; Yuefei Huang (Ocean & Coastal Management, 2024)

Separation mechanism of apatite and dolomite with flotation depressant konjac glucomannan - Lin Jing; Kai Xue; Jia Tian; Xi Zhang; Donghui Wang; Wenjun Guo; Zhimin Ma; Longhua Xu (Minerals Engineering, 2024)

Highly efficient treatment of tetracycline using coupled electro-Fenton and electrocoagulation process: Mechanism and toxicity assessment - Feng Yan; Xin Xu; Lili An; Wenjun Du; Wendi Shen; Kun-Lin Yang; Jianfeng Ye; Ruihua Dai (Chemosphere, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

In situ visualization of polycyclic aromatic hydrocarbon hydrothermal decomposition process utilizing planar induced fluorescence: A mechanistic analysis - Xiangjin Meng; Hongchao Dai; Wenjun Lin; Hongfang Liu; Xingang Qi; Xiao Cai; Jinhua Wang; Zuohua Huang; Hui Jin; Liejin Guo (Chemical Engineering Journal, 2024)

Mutagenesis and fluorescence-activated cell sorting of oleaginous Saccharomyces cerevisiae and the multi-omics analysis of its high lipid accumulation mechanisms - Xiaotong Ji; Lin Chen; Guanpin Yang; Chunlei Tang; Wenjun Zhou; Tianzhong Liu; Xuefeng Lu (Bioresource Technology, 2024)

Effect of urban street canyon aspect ratio on fire-induced air pollutants dispersion under cross wind - Shengzhong Zhao; Junhao Yu; Haoran Yang; Imad Obadi; Tiantian Xu; Fei Wang; Lin Xu; Wenjun Lei (Atmospheric Pollution Research, 2024)

N6-methyladenosine modified lncRNAs signature for stratification of biochemical recurrence in prostate cancer - Yingke Liang; Wenjun Yin; Zhouda Cai; Hongwei Luo; Qinwei Liu; Chuanfan Zhong; Jiahong Chen; Zhuoyuan Lin; Yaqiang Huang; Zhenguo Liang; Junhong Deng; Weide Zhong; et al. (Human Genetics, 2024)

High-temperature energy storage with a new tri-layers polymer composites via hybrid assembly engineering - Fei Wen; Hongbin Yuan; Mengquan Jiang; Pingan Yang; Jian Wang; Lin Zhang; Lili Li; Gaofeng Wang; Wenjun Li; Wei Wu; Zhonghui Shen; Shujun Zhang (Chemical Engineering Journal, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Kidney Function and Cardiovascular Disease: Evidence from Observational Studies and Mendelian Randomization Analyses - Wenjun Yang; Xuemei Wu; Manying Zhao; Jianying Hu; Chenhao Lin; Zhendong Mei; Jing Chen; Xu-jie Zhou; Sheng Nie; Jing Nie; Xiang Gao; Yan Zheng; et al. (Phenomics, 2024)

The joint effects of mixture exposure to multiple meteorological factors on step count: A panel study in China - Ziqiang Lin; Mengmeng Wang; Junrong Ma; Yingyin Liu; Wayne R. Lawrence; Shirui Chen; Wangjian Zhang; Jianxiong Hu; Guanhao He; Tao Liu; Ming Zhang; Wenjun Ma (Environmental Pollution, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

Establishment and Evaluation of Exosomes-Related Gene Risk Model in Hepatocellular Carcinoma - Lin Zhu; Yan Lou; Qiyu Xiao; Ling Wang; Guodong Chen; Wenjun Yang; Tengjiao Wang (Biochemical Genetics, 2024)
Hepatocellular carcinoma (HCC) is a challenging disease to evaluate in terms of prognosis, requiring close attention to the prognosis of HCC patients. Exosomes have been shown to play an important role in HCC development and have significant potential in managing HCC patient prognosis, as they are detectable in patients’ blood. By using small extracellular vesicular RNA, liquid biopsies can reflect the underlying physiological and pathological status of the originating cells, providing a valuable assessment of human health. No study has explored the diagnostic value of mRNA expression changes in exosomes for liver cancer. The present study investigated establishing a risk prognosis model based on mRNA expression levels in exosomes from blood samples of liver cancer patients and evaluated its diagnostic and prognostic value, providing new targets for liver cancer detection. We obtained mRNA data from HCC patients and normal controls from the TCGA and exoRBase 2.0 databases and established a risk prognostic assessment model using exosomes-related risk genes selected through prognostic analysis and Lasso Cox analysis. The patients were divided into high-risk and low-risk groups based on median risk score values to validate the independence and evaluability of the risk score. The clinical value of the model was further analyzed using a nomograph model, and the efficacy of immunotherapy and cell-origin types of prognostic risk genes were further assessed in the high- and low-risk groups by immune checkpoint and single-cell sequencing. A total of 44 genes were found to be significantly associated with the prognosis of HCC patients. From this group, we selected six genes ( CLEC3B , CYP2C9 , GNA14 , NQO1 , NT5DC2 , and S100A9 ) as exosomal risk genes and used them as a basis for the risk prognosis model. The clinical information of HCC patients from the TCGA and ICGC databases demonstrated that the risk prognostic score of the model established in this study was an independent prognostic factor with good robustness. When pathological stage and risk prognostic score were incorporated into the model to predict clinical outcomes, the nomograph model had the best clinical benefit. Furthermore, immune checkpoint assays and single-cell sequencing analysis suggested that exosomal risk genes were derived from different cell types and that immunotherapy in the high-risk groups could be beneficial. Our study demonstrated that the prognostic scoring model based on exosomal mRNA was highly effective. The six genes selected using the scoring model have been previously reported to be associated with the occurrence and development of liver cancer. However, this study is the first to confirm that these related genes existed in the blood exosomes, which could be used for liquid biopsy of patients with liver cancer, thereby avoiding the need for puncture diagnosis. This approach has a high value in clinical application. Through single-cell sequencing, we found that the six genes in the risk model originate from multiple cell types. This finding suggests that the exosomal characteristic molecules secreted by different types of cells in the microenvironment of liver cancer may serve as diagnostic markers.

Regulating electronic structure of Fe single-atom site by S/N dual-coordination for efficient Fenton-like catalysis - Huiwang Dai; Zhendong Zhao; Kun Wang; Fanxu Meng; Daohui Lin; Wenjun Zhou; Dingjiang Chen; Ming Zhang; Dongye Yang (Journal of Hazardous Materials, 2024)

Warming and wetting-induced soil acidification triggers methanotrophic diversity loss and species turnover in an alpine ecosystem - Chaonan Li; Changting Wang; Ping Zou; Lin Xu; Haijun Liao; Nan Lan; Li Lei; Wenjun Xiong; Weidong Kong; Junming Wang; Xiangzhen Li (CATENA, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

A novel low sampling rate and cost-efficient active sampler for medium/long-term monitoring of gaseous pollutants - Zhiyuan Wang; Tao Yu; Jin Ye; Lei Tian; Bencheng Lin; Wenjun Leng; Cong Liu (Journal of Hazardous Materials, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

Activation of peroxymonosulfate by Cu–Ni–Fe layered double oxides for degradation of butyl 4-hydroxybenzoate: Synergistic effect of oxygen vacancy and Cu(I) - Huiwang Dai; Jingyi Zhu; Fanxu Meng; Daohui Lin; Wenjun Zhou; Dingjiang Chen; Ming Zhang; Qingqing Wang (Chemosphere, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Study on Improving the Performance of Traditional Medicine Extracts with High Drug Loading Based on Co-spray Drying Technology - Zhe Li; Wanghai Peng; Lin Zhu; Wenjun Liu; Lingyu Yang; Lihua Chen; Abid Naeem; Weifeng Zhu; Yi Feng; Liangshan Ming (AAPS PharmSciTech, 2023)

L-theanine regulates the immune function of SD rats fed high-protein diets through the FABP5/IL-6/STAT3/PPARα pathway - Yangling Zhang; Yuxin Song; Jiao Zhang; Lanlan Li; Lin He; Jiahui Bo; Zhihua Gong; Wenjun Xiao (Food and Chemical Toxicology, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Influence of sidewall restriction on flame characteristics of double fires in a channel - Shengzhong Zhao; Kai Du; Yongzheng Yao; Fei Wang; Miaocheng Weng; Lin Xu; Wenjun Lei (Tunnelling and Underground Space Technology, 2023)

A hybridized continuum-discontinuum modeling for investigating the fracture and energy evolution characteristics of rock mass under sequential explosive detonation using a bilinear cohesive fracture model - Qindong Lin; Xinguang Zhu; Jianfei Yuan; Chun Feng; Yundan Gan; Wenjun Jiao; Yulei Zhang (Computers and Geotechnics, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Berberine inhibits gluconeogenesis in spontaneous diabetic rats by regulating the AKT/MAPK/NO/cGMP/PKG signaling pathway - Ming Lu; Yanpeng Wang; Yuanye Jiang; Cuiping Zhang; Hongping Wang; Wenjun Sha; Lin Chen; Tao Lei; Limei Liu (Molecular and Cellular Biochemistry, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Characterization and distribution of polybrominated diphenyl ethers in shellfish in Shenzhen coastal waters and assessment of human health risks - Chunxue Yang; Yousheng Jiang; Wenjun Zhao; Jinling Peng; Yuan Liu; Xiaoshi Lin; Jianqing Zhang (Marine Pollution Bulletin, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Insight into the effect of pyrolysis temperature on photoreactivity of biochar-derived dissolved organic matter: Impacts of aromaticity and carbonyl groups - Hanzhuo Luo; Eydhah Almatrafi; Wenjun Wang; Yang Yang; Danlian Huang; Weiping Xiong; Min Cheng; Chengyun Zhou; Yin Zhou; Qing Lin; Guoge Fang; Guangming Zeng; et al. (Science of The Total Environment, 2023)

Effect of peracetic acid generation in hydrogen peroxide-acetic acid pretreatment on production of xylooligosaccharides from poplar by organic acid hydrolysis - Zihe Lin; Wenjun Ying; Peiyao Wen; Zhina Lian; Junhua Zhang (Bioresource Technology, 2023)

Heterotrophic modification of Phaeodactylum tricornutum Bohlin - Wenlei Zhang; Wenjun Zhou; Si Jiang; Yanyan Wang; Lin Chen; Guanpin Yang; Tianzhong Liu (Algal Research, 2023)

Surface patterns of mortar plates influence Spirulina platensis biofilm attached cultivation: Experiment and modeling - Yongqiang Wang; Lu Li; Danyue Zhao; Wenjun Zhou; Lin Chen; Ge Su; Zhaohui Zhang; Tianzhong Liu (Algal Research, 2023)

Black carbon emissions and reduction potential in China: 2015–2050 - Wenjun Wang; Nina Khanna; Jiang Lin; Xu Liu (Journal of Environmental Management, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Laminar flame speeds of cyclic hydrocarbon fuels: Effect of unsaturation - Hu Liu; Wenjun Lin; Qianqian Li; Haoran Zhao; Zuohua Huang (Fuel, 2023)

Experiments and cellular automata simulation reveal light/carbon transportation and growth mechanism of Chlorella vulgaris biofilm in attached cultivation - Lu Li; Yongqiang Wang; Lili Gao; Wenjun Zhou; Lin Chen; Zhaohui Zhang; Tianzhong Liu (Chemical Engineering Journal, 2023)

Structural modification enhances the electrochemical performance for organic cathode materials - Shuai Liu; Fei Peng; Yilin Lin; Wenjun Zhou; Weiwei Huang (Chemical Engineering Journal, 2023)

An ultra-sensitive and specific nanoplasmonic-enhanced isothermal amplification platform for the ultrafast point-of-care testing of SARS-CoV-2 - Juxiang Liu; Ping Chen; Xulong Hu; Liping Huang; Zhi Geng; Hao Xu; Wenjun Hu; Lin Wang; Ping Wu; Gang L. Liu (Chemical Engineering Journal, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Characteristics of the chemical composition and source apportionment of PM2.5 for a one-year period in Wuhan, China - Xiaoyu Zhang; Guixiang Ji; Xiaowu Peng; Lingya Kong; Xin Zhao; Rongrong Ying; Wenjun Yin; Tian Xu; Juan Cheng; Lin Wang (Journal of Atmospheric Chemistry, 2022)

3D geomechanics modeling of Indonesia B oilfield and its application in wellbore stability - Wenjun Cai; Jingen Deng; Yongcun Feng; Hai Lin; Yanguang Yuan; Dongdong Liu (Arabian Journal of Geosciences, 2022)

MS1 is essential for male fertility by regulating the microsporocyte cell plate expansion in soybean - Xiaolong Fang; Xiaoyuan Sun; Xiangdong Yang; Qing Li; Chunjing Lin; Jie Xu; Wenjun Gong; Yifan Wang; Lu Liu; Limei Zhao; Baohui Liu; Jun Qin; et al. (Science China Life Sciences, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Nuclear envelope integrity, DNA replication, damage repair and genome stability - Wenjun Pu; Haihui Zhang; Peiwu Qin; Lin Deng (Genome Instability & Disease, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Ferrous iron-induced increases in capitate glandular trichome density and upregulation of CbHO-1 contributes to increases in blinin content in Conyza blinii - Tianrun Zheng; Maojia Wang; Junyi Zhan; Wenjun Sun; Qin Yang; Zhiyi Lin; Tongliang Bu; Zizhong Tang; Chenglei Li; Jun Yan; Zhi Shan; Hui Chen (Planta, 2020)

Preparation of high-purity R-phycoerythrin and R-phycocyanin from Pyropia yezoensis in membrane chromatography - Fan Zang; Song Qin; Chengbo Ma; Wenjun Li; Jian Lin (Journal of Applied Phycology, 2020)

Biosynthesis of phycocyanobilin in recombinant Escherichia coli - Chengbo Ma; Wenjun Li; Baosheng Ge; Jian Lin; Song Qin (Journal of Oceanology and Limnology, 2020)

Catechins enhance skeletal muscle performance - Penghui Li; Ailing Liu; Wei Xiong; Haiyan Lin; Wenjun Xiao; Jianan Huang; Sheng Zhang; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2020)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Effect of bisphosphonates on overall survival in subgroups of patients with prostate cancer - Congcong Wu; Wenjun Chen; Jian Wu; Xi Zhang; Xuanzhang Huang; Ruifang Lin; Baoling Zhu; Hua Jiang (Clinical & Experimental Metastasis, 2019)

Klotho recovery by genistein via promoter histone acetylation and DNA demethylation mitigates renal fibrosis in mice - Yanning Li; Fang Chen; Ai Wei; Fangfang Bi; Xiaobo Zhu; Shasha Yin; Wenjun Lin; Wangsen Cao (Journal of Molecular Medicine, 2019)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

In vitro remodeling and structural characterization of degradable polymer scaffold-based tissue-engineered vascular grafts using optical coherence tomography - Wanwen Chen; Junqing Yang; Wenjun Liao; Jiahui Zhou; Jianyi Zheng; Yueheng Wu; Dongfeng Li; Zhanyi Lin (Cell and Tissue Research, 2017)

Comparison of the effectiveness of resistance training in women with chronic computer-related neck pain: a randomized controlled study - Xiao Li; Caina Lin; Cuicui Liu; Songjian Ke; Qing Wan; Haijie Luo; Zhuxi Huang; Wenjun Xin; Chao Ma; Shaoling Wu (International Archives of Occupational and Environmental Health, 2017)

Eburicoic acid from Laetiporus sulphureus (Bull.:Fr.) Murrill attenuates inflammatory responses through inhibiting LPS-induced activation of PI3K/Akt/mTOR/NF-κB pathways in RAW264.7 cells - Junzhi Wang; Pan Zhang; Haibo He; Xinxin Se; Wenjun Sun; Beiyan Chen; Lin Zhang; Ximing Yan; Kun Zou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

TGF-β induces miR-30d down-regulation and podocyte injury through Smad2/3 and HDAC3-associated transcriptional repression - Lin Liu; Wenjun Lin; Qin Zhang; Wangsen Cao; Zhihong Liu (Journal of Molecular Medicine, 2016)

Short-term effects of multiple ozone metrics on daily mortality in a megacity of China - Tiantian Li; Meilin Yan; Wenjun Ma; Jie Ban; Tao Liu; Hualiang Lin; Zhaorong Liu (Environmental Science and Pollution Research, 2015)

Protective effect of berberine against myocardial ischemia reperfusion injury: role of Notch1/Hes1-PTEN/Akt signaling - Liming Yu; Feijiang Li; Guolong Zhao; Yang Yang; Zhenxiao Jin; Mengen Zhai; Wenjun Yu; Lin Zhao; Wensheng Chen; Weixun Duan; Shiqiang Yu (Apoptosis, 2015)

How much does latitude modify temperature–mortality relationship in 13 eastern US cities? - Jianpeng Xiao; Ji Peng; Yonghui Zhang; Tao Liu; Shannon Rutherford; Hualiang Lin; Zhengmin Qian; Cunrui Huang; Yuan Luo; Weilin Zeng; Cordia Chu; Wenjun Ma (International Journal of Biometeorology, 2015)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

Breeding, economic traits evaluation, and commercial cultivation of a new Saccharina variety “Huangguan No. 1” - Fuli Liu; Xiutao Sun; Feijiu Wang; Wenjun Wang; Zhourui Liang; Zhelong Lin; Zhian Dong (Aquaculture International, 2014)

Cyclin D1 polymorphism and oral cancer: a meta-analysis - Wenjun Wang; Yuming Zhao; Jie Yang; Bichen Lin; Haiyong Gu; Xiaoqing Cao; Lihong Ge (Molecular Biology Reports, 2013)

Salusins protect myocardium against ischemic injury by alleviating endoplasmic reticulum stress - JianFei Wang; Yin Wang; ShiFu Shan; TianTian Hu; HuYan Chen; Jing Tian; AnJing Ren; Xu Zhou; WenJun Yuan; Li Lin (Science China Life Sciences, 2012)

Molecular responses to the fungal pathogen Gibberella fujikuroi in the leaves of chewing cane (Saccharum officinarum L.) - Sheng Lin; Yifei Zhou; Guanshui Chen; Yang Zhang; Yanyun Zhang; Wenjun Ning; Daren Pan (Sugar Tech, 2010)